Utilizing granulated rubber in soil compression: a new possibility for better waste disposal (Research, Society and Development, 2020)
This research has the objective of presenting an experimental study of soil behavior that had crushed rubber from old tires added to it, in order to promote a new destination for these solid wastes. Small percentages of granulated rubber were added to the compacted soil samples from grinding old tires without the metal part of their structure. In order to simulate soil compression in infrastructure works, specifically roads, massive characterization tests were performed, namely; real density (DR), liquidity limit (LL), plasticity (LP), index plasticity (IP) and compaction assays (dry specific soil mass and optimum moisture levels). The tests were standardize d to quantify the behavior towards the disposal of these materials maintaining the initial quality of the soil of Teresina, Piauí or any other region with similar characteristics where standard soil (without additives) and with mixtures with 1% to 5% of granulated tires. In the results it was observed that by adding small percentages, there were no significant changes in the degree of soil compaction and the possibility of them being discarded in compacted soils without loss in the quality of the massif. This would be a way of sustainable disposal of rubbers with the purpose of reducing the environmental impacts that these types of waste of generate for the environment.